2013
DOI: 10.1145/2461912.2461972
|View full text |Cite
|
Sign up to set email alerts
|

Depicting stylized materials with vector shade trees

Abstract: Figure 1: We describe Vector Shade Trees that represent stylized materials as a combination of basic shade nodes composed of vector graphics primitives (a). Combining these nodes allows the depiction of a variety of materials while preserving traditional vector drawing style and practice. We integrate our vector shade trees in a vector drawing tool that allows users to apply stylized shading effects on vector line drawings (b,c). This pdf contains png versions of vector art to avoid viewer compatibility proble… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…Another extension of our work would consist in casting the decompositing problem as a global optimisation across multiple layers to better capture residual colour variations, potentially using our greedy solution as an initial solution. Finally, our layered representation could facilitate the creation of vector shade trees [LMPB*13] from existing drawings and photographs, which would represent a first step towards the capture and transfer of material appearance in illustrations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another extension of our work would consist in casting the decompositing problem as a global optimisation across multiple layers to better capture residual colour variations, potentially using our greedy solution as an initial solution. Finally, our layered representation could facilitate the creation of vector shade trees [LMPB*13] from existing drawings and photographs, which would represent a first step towards the capture and transfer of material appearance in illustrations.…”
Section: Discussionmentioning
confidence: 99%
“…The key observation that guides our approach is that complex images often can be explained with just a few simple layers. In fact, researchers have shown that the human visual system infers transparent layers if they result in a simpler explanation of the visual stimuli [Ade93,LZW02]. Vector graphics represent transparency using alpha compositing [PD84], which composites the foreground colour F over the background B using the foreground's opacity channel α:…”
Section: Image Decompositionmentioning
confidence: 99%
“…Although some high‐level functionality are supported in these systems, such as image vectorisation tools, the suite of tools available are primarily low‐level tools for creating, manipulating, and organising vector primitives. While low‐level vector representations are still an active area of research [DRvdP14, SVG16], there is also an incentive for high‐level vector tools [LZC11, LMPB*13, GBLM16]. However, to our knowledge, high‐level manipulation and synthesis for layered or component‐based vector graphics have not been previously proposed.…”
Section: Related Workmentioning
confidence: 99%
“…Our underlying representation is inspired by Cook's Shade Trees [5]. A similar approach has been employed for 2D illustrations [20]. The system architecture and programming model have similarities to RenderMan [6] and shading languages [15].…”
Section: Data-driven Solid Texture Synthesismentioning
confidence: 99%